Characterising the immune microenvironment in liposarcoma, its impact on prognosis and the impact of radiotherapy. Issue 1 (20th October 2020) - Snow, Hayden; Mitchell, Catherine; Hendry, Shona; McKinley, Madeleine; Byrne, David; Ngan, Sam; Chander, Sarat; Chu, Julie; Desai, Jayesh; Bae, Susie; Henderson, Michael; Choong, Peter; et al.
Abstract: Background and Objectives: Limited literature exists examining the immune microenvironment in liposarcoma, particularly with regard to the impact of radiotherapy. A major problem is the lack of scoring system for the tumour‐infiltrating lymphocytes (TILs) in sarcoma. This study aims to describe the immune environment pre‐ and postradiotherapy and identify the optimal immune infiltrate scoring system for sarcoma. Methods: Thirty‐nine paired tissue samples (pre‐ and postradiotherapy) from patients with liposarcoma were scored by two pathologists for TILs using pre‐existing systems (for breast cancer and melanoma) and compared for interobserver reliability. Immunohistochemical staining was performed for various immune markers. Results: The TIL scoring system for breast cancer yielded perfect agreement ( κ = 1.000). 21% of patients had increased TILs after radiotherapy, 87.5% of whom had dedifferentiated liposarcoma. Immune suppressor expression was increased frequently after radiotherapy (CD68 increased in 59.4%, PD‐L1 increased in 25%). Immune effector expression (CD8) was unchanged in 84.4%. Conclusions: Breast cancer TIL scoring is reproducible in liposarcoma and has high interobserver reliability. Radiotherapy was observed to have a limited impact on immune effectors but seemed to have more impact in upregulating immune suppressors, suggesting radiotherapy may contribute to disease control through immunomodulatory effects. Dedifferentiated liposarcoma represents a uniquely responsive subtype.